The water of the Jordan Valley : bscarcity and deterioration of groundwater and its impact on the regional development - Hötzl, Heinz. (Springer, 2017)
Natural saline water, waste water, and irrigation return flow endanger the groundwater aquifers in the Rift. In the long run this will ruin the socio-economic backbone of the settlements in the area. Sustainability of the water resources will only be achieved when the process of water replenishment and its underground flow is understood and water extraction is regionally controlled. Rare earth element and spider patterns are presented as new tools for studying the hydrology. Progress in 3-D modelling of groundwater flow proved successfully the impact of pumping on the surroundings of wells and overexploitation of aquifers.